Internal RNA Replication Elements are Prevalent in Tombusviridae - Nicholson, Beth L.; Lee, Pui Kei K.; White, K Andrew (Frontiers in Microbiology, 2012)
Internal replication elements (IREs) are RNA structures that are present at internal positions in the genomes of different types of plus-strand RNA viruses. Members of the genus Tombusvirus (family Tombusviridae) contain an IRE within the polymerase coding region of their genomes and this RNA element participates in both genome targeting to sites of replication and replicase complex assembly. Here we propose that other members of the virus family Tombusviridae also possess comparable IREs. Through sequence and structural analyses, candidate IREs in several genera of this family were identified, including aureusviruses, necroviruses, carmoviruses, and pelarspoviruses. The results from subsequent mutational analysis of selected proposed IREs were consistent with a critical role for these structures in viral genome accumulation during infections. Our study supports the existence of IREs in several genera in Tombusviridae and points to previously unappreciated similarities in genome replication strategies between members of this virus family.